ANALISIS ZAT PEWARNA RHODAMIN B PADA SAUS CABAI YANG BEREDAR DI KAMPUS UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG (Jurnal Biota, 2017)
Chili sauce is one of the most popular food product because it was used as food complement. Generally in processing manufacture chili sauce added coloring substance, so product colour interesting. Nowadays more and more food manufacturers use dye that have been banned use. Rhodamine B dye in the form of a crystalline powder green or reddish purple, odorless and dissolves easily in bright red solution berfluoresan as textile dyes. Rhodamin b is still no food products were found to countain rhodamine B dye such as crackers, sauces, ice and other pastries. Rhodamin B is a synthetic dye that was banned for use in foods and is certified as a hazardous material according to Minister of Healthy of Indonesian Republic No. 722/Menkes/Per/IX/1998. Rhodamin B is carcinogenic, in the long term use can cause liver damage, kidney inflammation, and cancer. The kind of research this used a quantitative approach with the experimental methods laboratory. The purpose of this study was to determine whether there rhodamin B in the test samples using thin layer chromatography (TLC). The result shows that 7 examined samples doesn’t contain rhodamin B and and shows f count smaller than f table (F count< F table) (3,61< 3,71). Synthetic dyes are contained in most of the analyzed samples are dyes that allow its use for food by the Regulation of the Minister of Health of Indonesia such as ponceau 4R and amarant and Contribution of research given by researchers of worksheets students and implementation plan learning